Liquid-liquid mixing in stirred vessels: a review - Afshar Ghotli, R.; Abdul Raman, Abdul Aziz; Ibrahim, Shaliza; Baroutian, S. (Taylor & Francis, 2013)
Liquid-liquid mixing is a key process in industries that is commonly accomplished in mechanical agitation systems. Liquid-liquid mixing performance in a stirred tank can be evaluated by various parameters, namely minimum agitation speed, mixing time, circulation time, power consumption, drop size distribution, breakup and coalescence, interfacial area, and phase inversion. The importance of these liquid-liquid mixing parameters, the measurement method, and the results are discussed briefly. Input parameters such as impeller type, power number, flow pattern, number of impellers, and dispersed phase volume fraction, in addition to physical properties of phases such as viscosity and density, are reviewed. Scale-up aspects are also included. Â© 2013 Copyright Taylor and Francis Group, LLC.